Acute and chronic effects of stretching on running economy: A systematic review with meta-analysis - Warneke, K.; Zechner, M.; Siegel, S. D.; Jochum, D.; Brunssen, L.; Konrad, A. (Sports Medicine - Open, 2025)
Background Running economy (RE) determines the performance of endurance athletes. While stretching has been practised for decades, and is still one common integral component of warm-up routine, muscle stretching is also associated with decreased stiffness. For RE energy storage in the tendons which is accompanied with stiffness is of crucial importance. In turn, avoidance of pre-running stretching was frequently recommended. Although some studies supported this recommendation, the evidence is controversial. Nevertheless, yet, no systematic review on the effects of stretching on RE with effect size (ES) quantification was performed. Consequently, with this systematic review with meta-analysis, we aim to provide the first overview on this topic.